The impact of personal perception on the identification of tattoo pattern in human identification. (May 2019) - Kate Brookes, Georgina; Thompson, Tim
Abstract: Tattoos and body modifications have a significant role to play in the identification of individuals in a variety of forensic contexts. Despite this, little work has explicitly examined this topic. The aim of this study was to examine whether personal perception has an influence on the identification of tattoo images. A questionnaire was constructed containing a variety of tattoo images and distributed randomly, resulting in two hundred and eleven participant responses. The results indicated that the perception of tattoos has a high margin for error and interpretation. The conclusion of the study argues that a perception issue exists amongst individuals, however further work needs to be carried out to establish the degree of variation. Highlights: The questionnaire results show that individuals perceive tattoos differently. There seems to be no obvious trend between the answers and the images perceived. The FARO Gage testing was able to produce an image similar to the original tattoo. The FARO Gage apparatus proved to be very simple, effective and accurate.